(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article offers an in-depth exploration of the Renaissance period in the lives of the peoples of Central Asia, with a specific focus on the contributions of Uzbek ancestors to world civilization during the 9th to 12th centuries. It examines the cultural, intellectual, and economic achievements of the Uzbek people during this era, highlighting their role in the flourishing of trade, scholarship, and artistic expression along the Silk Road. Additionally, the article sheds light on the enduring legacy of Uzbek scholars, poets, artisans, and rulers in shaping the broader Islamic civilization and their influence on global history and heritage. Through a meticulous analysis of historical sources, archaeological findings, and cultural artifacts, the article provides valuable insights into the dynamic and diverse contributions of Uzbek ancestors to the Renaissance period in Central Asia and their impact on the trajectory of human civilization.